Dampak Potensial Implementasi Buku Ajar Berbasis Problem Based Learning Pada Mata Kuliah Pendidikan Kependudukan Dan Lingkungan Hidup - Alfiandra Alfiandra; Sri Artati Waluyati; Sani Safitri; Kurnisar Kurnisar; nuraini nuraini (Jurnal Civic Hukum, 2023)
This study aims to analyze and determine the potential impact of implementing problem-based learning (PBL) textbooks on Population and Environmental Education (PKLH) courses on student learning outcomes and critical thinking skills in the PPKn Study Program, FKIP, Sriwijaya University. This study uses a quantitative descriptive research method. Learning outcomes are seen from test results, while critical thinking skills are seen from the results of observations on the ability to identify, define, explore, and integrate problems. The results showed that there was an increase in the average student learning outcomes between before and after using PBL-based textbooks with a post-test score of 62.89 increasing to 87.63 during the post-test with a difference in score of 24.74 points. The results of observations on students' critical thinking skills before and after using PBL-based PKLH textbooks showed an increase in the critical thinking ability score, from 70.04 to 90.80 with an n gain value of 0.69 (high category).